PENGARUH TEKNIK RELAKSASI OTOT PROGRESIF TERHADAP KADAR GULA DARAH PADA PASIEN DM TIPE 2 - Yuliani, Tika; Hutasoit, Masta (Universitas Jenderal Achmad Yani Yogyakarta, 2013)
Background: Diabetes Mellitus (DM) is a degenerative disease that is often not identified until its complications arise. It is also known that DM is a chronic disease that cannot be cured because one of  the precipitating factors of hyperglycemia in patients who have Type 2 DM is emotional distress.  Therefore continuous treatment to control hyperglycemia should be identified. Progressive muscle relaxation technique is one of complementary therapies which works by decreasing the muscle tone to enhance patient?s relaxation state. Objective: To identify the effect of progressive muscle relaxation techniques on blood sugar in patients who have type 2 DM. Methods: The study used a quasy-experimental research design. 12 participants who met the inclusion criteria were recruited. Paired sample t-tests with p<0.05 was used to investigate the mean difference of blood sugar level before and after intervention. Result: The decreased of blood sugar levels in patients who got the intervention  (p= 0,00)  is  higher  than when there is no intervention progressive muscle relaxation technique (p= 0,00). Conclusion: Progressive muscle relaxation technique is effective to decrease blood sugar level of type 2 DM patients. Key words: Diabetes Mellitus, progressive muscle relaxation technique, complementary therapy.